PERBANDINGAN FERTILITAS SERTA SUSUT, DAYA DAN BOBOT TETAS AYAM KAMPUNG PADA PENETASAN KOMBINASI - Dimas Wicaksono; Tintin Kurtini; Khaira Nova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2013)
Hatching chicken eggs can be grouped into three ways namely hatching naturally with the help of wild duck, artificial hatching machine, and a combination of natural and artificial means. Hatching allegedly using a combination of ways to improve hatchability chicken. The purpose of this study was to determine the combination of chicken egg hatching process better by fertility and shrinkage, power, and weight of hatching. This study using student t-test on the real level of 5% with 2 treatments namely P1 (7 days incubation at parent wild duck and then proceed to the hatching machine) and P2 (10 days incubation at parent wild duck and then proceed to the hatching machine). Each treatment consists of 20 units and each experimental trial consisted of 5 eggs. Incubation at parent entok for 7 days and then proceed to the hatching machine indicates fertility and hatchability better (P <0,05) compared with the parent wild duck incubation for 10 days, but the effect was not significant (P> 0,05) against shrinkage and weight hatching. Kata kunci : Penetasan kombinasi, fertilitas, susut tetas, daya tetas, bobot tetas